Mathematical knowledge for teaching as a didactic praxeology - Pansell, Anna (Frontiers in Education, 2023)
It is widely acknowledged that teachers' work has both practical and theoretical dimensions, both praxis and logos and that therefore teacher education should integrally address both dimensions. However, as I will argue in this paper, existing discourses for describing the mathematical knowledge of teachers and what it takes to become competent in it are not always clear to what extent these discourses address knowledge about the practices of mathematics teaching, or theories that provide arguments for the practices. Specifically, I argue for extending a coordination of the framework of Mathematical Knowledge for Teaching (MKT) by coordinating with the analytical distinction of logos and praxis combined in the practices of teaching. And I will back this argument with examples of the proposed categories of the adjusted framework from the existing body of work in mathematics education. This serves to exemplify and further develop the categories of the proposed framework. Each category of the proposed framework, whether concerning a teaching method or a theoretical consideration, was indeed exemplified by some concept, approach, or perspective from the field of mathematics education. The framework will prove useful in engaging mathematics teacher education discursively, for instance in analyzing teacher education materials to determine the extent to which they offer mere methods, theoretical arguments, or a connection of both.